Streptomyces lydicus M01 Regulates Soil Microbial Community and Alleviates Foliar Disease Caused by Alternaria alternata on Cucumbers - Wang, Mingxuan; Xue, Jian; Ma, Junjie; Feng, Xiaohai; Ying, Hanjie; Xu, Hong (Frontiers in Microbiology, 2020)
Due to the adverse effect on the environment caused by excessive use of chemical fertilizers, the development of sustainable agriculture attracts a growing demand of biological based fertilizers composed of living microorganisms. In this study, an Actinobacteria Streptomyces lydicus M01 was isolated from the rhizosphere soil of Pyrus calleryana. This strain effectively promoted the plant growth and suppressed a foliar disease caused by Alternaria alternate on cucumbers. S. lydicus M01 exhibited growth promoting characteristics such as phosphate solubilization, IAA secretion, siderophore and ACC deaminase production. Through Illumina sequencing of the 16S rRNA gene and ITS gene of the soil microbes, we found that the application of S. lydicus M01 altered the composition of the microbial community by promoting beneficial groups, including bacteria genera Pseudarthrobacter, Sphingomonas, Rhodanobacter and Pseudomonas, fungi genera Fusicolla, Humicola, Solicoccozyma and Paraphaeosphaeria. Most of these bacteria and eukaryotes exhibit positive effects on growth promotion, such as nutrient accumulation, auxin secretion, abiotic stress alleviation, biological control or bioremediation. Furthermore, studies on the ROS level and antioxidants of cucumber leaves revealed that S. lydicus M01 treatment reduced the ROS accumulation and increased the activities of antioxidases related with ROS scavenging, which indicated an enhanced disease resistance of cucumbers under biotic stress. Thus, our results suggest that the application of S. lydicus M01 can systemically affect plant microbiome interactions and represent a promising sustainable solution to improve agricultural production instead of chemical fertilizers.